Webinar Psikologi Perkembangan dalam Pembelajaran di Sekolah Dasar Era PJJ Covid-19 - Elin Herlina Kurniawan; Eksa Sulistianingrum; Haliman Ghani Ismail; Reny Nurandini; Saskia Khairunnisa Kurnia; Christina Mariella Sihombing; Hisny Fajrussalam; Mamad Kasmad; Gia Nikawanti (Jurnal Pengabdian Masyarakat PGSD, 2021)
The problem of teachers, especially in elementary schools, to follow up on the psychology of children that have occurred so far have not been resolved. Moreover, the Covid-19 outbreak which has hit the Indonesian nation, is increasing in number every day, thus require students to study online and unable to carry out face-to-face learning. In this pandemic, primary school or elementary school students were most affected subject. Innovations to know and explore further the developmental psychology of elementary school age children were potentially carried out through webinars. Elementary school teachers strongly questioned the continuity of developmental psychology of students while studying at home. To facilitate, the group 10 PPLSP Elementary School Teacher Education Program UPI Purwakarta Campus at Nagri Kaler 8 Elementary School, Purwakarta Regency, West Java Province held a service webinar for elementary school teachers in Purwakarta with the theme The Urgency of Counseling and Developmental Psychology in Learning in PJJ Era Elementary Schools. Covid-19. With the webinar, all teachers understand further the psychology of child development that has occurred